Q: How do you factor 3x2 plus 12x plus 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x2 + 12x = - 1 ie 3x2 + 12x + 1 = 0 has no rational roots. The irrational roots are [-12 +/- sqrt(132)]/6 = -3.915 and -0.085

The GCF of 12^2 + 18 - 36 is 6.

It is x^2 + 12x or x(x + 12).

-5 + 12x = 18x + 7Subtract 7 from each side:-12 + 12x = 18xSubtract 12x from each side:-12 = 6xDivide each side by 6:-2 = x

84

Related questions

3x2 + 12x = - 1 ie 3x2 + 12x + 1 = 0 has no rational roots. The irrational roots are [-12 +/- sqrt(132)]/6 = -3.915 and -0.085

The equation is equivalent to: -3x2 - 12x - 1 = 0 [you could change signs to get 3x2 + 12x + 1 = 0 but that is not required] The discriminant is (-12)2 - 4*(-3)(-1) = 144 - 12 = 132

You can find the x-coordinate of it's vertex by taking it's derivative and solving for zero: y = -3x2 + 12x - 5 y' = -6x + 12 0 = -6x + 12 6x = 12 x = 2 Now that we have it's x coordinate, we can plug it back into the original equation to find it's y coordinate: y = -3x2 + 12x - 5 y = -3(2)2 + 12(2) + 5 y = -12 + 24 + 5 y = 17 So the vertex of the parabola y = -3x2 + 12x - 5 occurs at the point (2, 17).

Factor. X^2 + 12X X(X + 12) = 0 X = 0 ------------- X + 12 = 0 X = - 12 --------------

If you mean: 3x^2+12x+12 = 0 then it has two equal solutions of -2

12x^2+24x+12 12(x^2+2x+1) 12(x+1)^2

-3x2 + 16x + 12 = -3x2 + 18x - 2x + 12 = -3x*(x - 6) - 2(x - 6) = -(3x + 2)*(x - 6)

If the equasion is 12x+6-8x-4x-3+12 then the answer is 15.

x3 + 3x2 - 4x -12 x2(x + 3) - 4(x + 3) (x2 - 4)(x+3)

The GCF of 12^2 + 18 - 36 is 6.

It is x^2 + 12x or x(x + 12).

-5 + 12x = 18x + 7Subtract 7 from each side:-12 + 12x = 18xSubtract 12x from each side:-12 = 6xDivide each side by 6:-2 = x